2010
DOI: 10.1177/1074840710376774
|View full text |Cite
|
Sign up to set email alerts
|

Families Suffering With HIV/AIDS: What Family Nursing Interventions Are Useful to Promote Healing?

Abstract: The purpose of this clinical research project was to examine the usefulness of a family nursing intervention program offered to families experiencing illness suffering related to HIV/AIDS. The interventions were based on the Family Caregiving Model and the Illness Beliefs Model. Sixteen Thai families with one or more family members living with HIV/AIDS were offered three to four family clinical sessions by an advanced practice family nurse. The audiotaped family clinical sessions and field notes were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…Consequently, no individual is to blame for a problem experienced within the family [18]. One qualitative study including 16 families living with HIV/AIDS showed that one response to family nursing systems interventions is an increased understanding of family dynamics which opens up for change and contributes to the families' health experiences and individual well-being [21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, no individual is to blame for a problem experienced within the family [18]. One qualitative study including 16 families living with HIV/AIDS showed that one response to family nursing systems interventions is an increased understanding of family dynamics which opens up for change and contributes to the families' health experiences and individual well-being [21]. …”
Section: Discussionmentioning
confidence: 99%
“…This may embrace change or modification of constraining beliefs and strengthening of facilitating beliefs, of finding alternative ways of talking about the family situation and the discovery of new meanings [15, 16]. A small but growing body of qualitatively designed outcome studies focusing on families' experiences points at these interventions to be a healing experience [17], improving family relationships [18, 19], alleviating experiences of suffering [20, 21], and psychologically empowering [22, 23]. …”
Section: Introductionmentioning
confidence: 99%
“…Broadly speaking, there has been little empirical research addressing the adaptation of evidence-based interventions to ensure their fit for specific cultures and communities [16]. Family relationships are important and family is a valuable resource of support and care for ill family members [17], especially in Thai culture [18]. Previous studies have identified challenges associated with cultural adaptations of interventions based on Western-based behavioral theories to non-Western contexts, where the former focuses more on individual agency, whereas the latter emphasizes collectivistic notions [19–21].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have primarily focused on family counselling interventions for chronic illness [11][12][13][14]. Three general goals that familyfocused interventions have been found to involve are: helping families cope with the challenges of chronic illness management, mobilizing family support and reducing intrafamilial suffering [15].…”
Section: Introductionmentioning
confidence: 99%
“…This study is a part of larger project on the quality and safety of emergency medical services in one hospital district serving 200, 000 inhabitants in Finland. Counselling is defined as goaloriented, research and evidence-based support and advice, whose purpose is to enhance the coping of patients and their family members during follow-up care at home [9,10].Earlier studies have primarily focused on family counselling interventions for chronic illness [11][12][13][14]. Three general goals that familyfocused interventions have been found to involve are: helping families cope with the challenges of chronic illness management, mobilizing family support and reducing intrafamilial suffering [15].…”
mentioning
confidence: 99%